can someone please help me?

Answer:
The answer is 27
Step-by-step explanation:
The reason being, you can solve this 2 ways.
1) Combine like terms, 7a-4a = 3a.
Now just substitute (a=9) into 3a.
3 * (9) = 27.
2) Or just substitute a = 9 into the original expression.
7 * (9) - 4 * (9)
= 63 - 36 = 27
Hello!
The correct answer is option four, 27.
We know that a = 9.
Because the a is right next to the 7 and the 4, this indicates that it is being multiplied.
7a - 4a
Substitute for the 'a'.
= 7(9) - 4(9)
= 63 - 36
= 27